Meningkatkan Fokus dan Motivasi Belajar Siswa melalui Pendekatan Hypno Teaching dalam Psikologi Pendidikan - Palenza, Nabila Rezky; Nirwana, Herman; N, Neviyarni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Focus and motivation to learn are two main factors that greatly influence student success in the learning process. The Hypno Teaching approach is an innovative learning method that combines light hypnosis techniques, relaxation, and positive suggestions to create a conducive learning atmosphere and improve students’ mental readiness. This article aims to review the literature related to the effectiveness of Hypno Teaching in improving students’ focus and motivation to learn based on educational psychology studies. The results of the study indicate that Hypno Teaching can improve focus and motivation to learn through relaxation mechanisms that reduce anxiety and positive suggestions that strengthen students’ intrinsic motivation. The implications of this approach are very relevant for teachers and education practitioners in creating more effective and enjoyable learning methods.